Effect of negative triangularity on peeling-ballooning instability. (2nd March 2023) - Qin, Chenchen; Mou, Maolin; Chen, Shaoyong; Li, Yongjian; Luo, Yang; Zhu, Limin; Dong, Liangkang; Tang, Changjian
Abstract: Experiments have achieved high confinement discharges in tokamaks with a negative triangularity (NT) plasma shape accompanied by a lower pedestal and smaller and more frequent edge localized modes (ELMs) compared with positive triangularity (PT). Some existing theories emphasize the linear instability variations result from the change of pedestal. However, NT can directly bring significant changes on magnetic field structures which may also influence the instability of ELMs. Based on a series of equilibria constructed with different triangularities and pressure profiles, the influence of NT on peeling-ballooning mode (P–B mode) is investigated. It is found that NT can increase the growth rates of low to intermediate n (toroidal mode number) modes in the linear stage and lead to a larger pedestal collapse in the nonlinear stage if its pressure profile is the same with the PT shape. Further analyses demonstrate that NT enlarges the unfavorable curvature area, which provides stronger driving source and larger unstable region for the instability. Meanwhile, the diamagnetic effect and local magnetic shear helps to stabilize high n modes in the linear phase, and the E × B shearing rate at the top of the pedestal contributes to suppress the transport of turbulence into the plasma core in the nonlinear phase for the NT shape. What's more, further simulations with different pedestal heights demonstrate that there exists a threshold value of pressure ratio, below which the ELM energy loss in NT shapes can be smaller than that in PT shapes, suggesting that the smaller energy loss with NT in experiment mainly results from the lower pedestal heigh. The results reveal behaviors of P–B modes and provide possible mechanisms for the phenomenon of lower pedestal height with negative triangularities in experiments.